2017
DOI: 10.11648/j.ajhc.20170303.11
|View full text |Cite
|
Sign up to set email alerts
|

<i>In-vitro</i> Antimicrobial, Anti-oxidant Activities and Cytotoxicty of <i>Carum carvi</i> L

Abstract: Carum carvi L. was used traditionally in different populations for many medical complains. The study was aimed to investigate antimicrobial, anti-oxidant activities and cytotoxicty of fixed oil of Carum carvi L. (seeds). The oil was extraction by petroleum ether (60-80°C) using a Soxhlet apparatus. The oil of Carum carvi L. seeds were tested against four standard bacterial species: two Gram-positive bacteria viz, Bacillus subtilis (NCTC 8236) and Staphylococcus aureus (ATCC 25923), two Gram-negative bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Great inhibitory effects of BPEO on several pathogens such as Staphylococcus aureus (ATCC 25923, ATCC 6538), Bacillus cereus (ATCC 11778), Listeria monocytogenes (ATCC 19112, ATCC 19118, ATCC 7644), Escherichia coli O157: H7 (ATCC 43894), Salmonella spp. (ATCC 13311; ATCC 14028) has been reported (Abdalaziz et al, 2017;Ehsani et al, 2016;Fallahi et al, 2010;Ghderi et al, 2014;Noori et al, 2014;Oroojalian et al, 2010;Rabiey et al, 2013). Findings of other related studies have been summarized in Table 3.…”
Section: Antibacterial Propertiesmentioning
confidence: 86%
See 1 more Smart Citation
“…Great inhibitory effects of BPEO on several pathogens such as Staphylococcus aureus (ATCC 25923, ATCC 6538), Bacillus cereus (ATCC 11778), Listeria monocytogenes (ATCC 19112, ATCC 19118, ATCC 7644), Escherichia coli O157: H7 (ATCC 43894), Salmonella spp. (ATCC 13311; ATCC 14028) has been reported (Abdalaziz et al, 2017;Ehsani et al, 2016;Fallahi et al, 2010;Ghderi et al, 2014;Noori et al, 2014;Oroojalian et al, 2010;Rabiey et al, 2013). Findings of other related studies have been summarized in Table 3.…”
Section: Antibacterial Propertiesmentioning
confidence: 86%
“…Many studies have been carried out in the field of antioxidant properties of extracts and essential oil of black Caraway which all indicated high antioxidant effects and scavenging ability of free radicals for this plant (Abdalaziz et al, 2017;Bamdad et al, 2006;Chizzola et al, 2014;Haghirogsadat et al, 2010;Samojlik et al, 2010). Essential oil and phenolic extract of black caraway show a good antioxidant and DPPH scavenging properties compared to BHT and BHA (Kapoor et al, 2010;Thippeswamy et al, 2013).…”
Section: Antioxidative Propertiesmentioning
confidence: 99%
“…Wild Cumin seeds have a number of compounds such as polyphenol, estragol, anethole, limonene, carvone, carvacrol, linalool, and monoterpene. The improved weight gain and feed efficiency of birds fed with WC seeds may be due to the presence of these compounds which have antibacterial and antioxidant effects (Thippeswamy et al 2013;Abdalaziz et al 2017). Additionally, we found that the apparent ileal digestibility of the nutrients was comparatively better improved in WC1.…”
Section: Discussionmentioning
confidence: 58%